A Model for Using Web-Oriented Automated Information Systems for the Formation and Development of the National Conceptual and Terminological Framework in Pedagogy and Psychology - Pinchuk, Olha (Educological discourse, 2025)
The development of models that combine the structured nature of classical encyclopedias with the flexibility of modern web-oriented solutions addresses the growing demand for automated information systems for knowledge storage and access. A survey of 232 respondents from various institutions of the National Academy of Educational Sciences of Ukraine was conducted to determine digital tools’ current status and development prospects in this field. This article presents a structural-functional model for utilizing web-oriented automated information systems to form and develop the national conceptual and terminological framework in pedagogy and psychology. The model is based on six key components: a database of concepts and terms, functional modules of the system, technological components, usage processes, user roles, and the external environment, which, among other things, includes access to external data sources. The external environment also involves different groups of users who provide feedback on the system’s performance. Unidirectional and bidirectional connections between its components ensure the model’s functionality. An example of an electronic industry encyclopedia is considered, which combines multi-level sources of information and provides adequate access to knowledge for the scientific and educational community. It has been established that at the current stage, there is a lack of focused discussion on the role of web-oriented automated information systems, particularly electronic encyclopedias, in knowledge accumulation and dissemination processes. The conclusions highlight the potential of digital platforms capable of meeting the need for structured weboriented automated information systems adapted to the field of education. Based on the structural-functional model presented, the author has proposed sequential steps for implementing the web-oriented automated information system “Ukrainian Electronic Encyclopedia of Education”.